2019
DOI: 10.2478/acve-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Artemisinin on Testis and Kidney Injury Induced by Doxorubicin

Abstract: Artemisinin, an antimalarial drug, has anticancer activity and possesses protective effects against several tissue injuries. The aim of the present study was to investigate the effects of artemisinin on doxorubicin-induced renal and testicular toxicity in rats. Doxorubicin was administered to rats at a single dose of 10 mg/kg body weight (b.w.) as a single intraperitoneal injection. Application of artemisinin was by using oral gavage feeding needle for 14 days at different specified doses (7 mg/kg and 35 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Regarding to the group treated with the carcinogen and doxorubicin drug, the following effect were observed, presence case degeneration in renal tubules, cell necrosis, lysis of cortical tubules, lymphocyte infiltration, glomerulus destroy ,tubules destroy, glomerular thickening. Basement membrane breakdown, epithelial cell degeneration tubules expansion and bleeding between the cells (figure2-E,F,G), these disorders may due to the effect the carcinogen and drug on the kidney tissue [22,26,31,32,33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to the group treated with the carcinogen and doxorubicin drug, the following effect were observed, presence case degeneration in renal tubules, cell necrosis, lysis of cortical tubules, lymphocyte infiltration, glomerulus destroy ,tubules destroy, glomerular thickening. Basement membrane breakdown, epithelial cell degeneration tubules expansion and bleeding between the cells (figure2-E,F,G), these disorders may due to the effect the carcinogen and drug on the kidney tissue [22,26,31,32,33].…”
Section: Resultsmentioning
confidence: 99%
“…for the group treated with doxorubicin drug, including thickening of the basement membrane, metaplasia of the epithelial lining of the tubules, bowman space expansion, complete dissolution in the lining of tubules and necrosis of medulla tubules, expansion of their lumen (figure2-H,I,J). High dose of doxorubicin causes acute toxic side effects in kidney tissue which in turn induced nephrotoxicity [29,33,34,35,36] . In addition , doxorubicin drug causes cell damage due to oxidative stress and this is consistent with [32] .…”
Section: Different Pathological Changes Have Been Observedmentioning
confidence: 99%
“…Previous studies showed that some oncogenic mutations cause apoptosis, cancer initiation, progression or metastasis. It is now well documented that most cytotoxic anticancer agents induce apoptosis, and defects in apoptotic pathways contribute to treatment failure (Ma et al, 2017;Tutun et al, 2019). Inflammation has a critical role in tumor progression and many cancers occur from sites of infection, inflammation, and chronic irritation (van Kempen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PE and PE‐CSNP treatment were administered by oral gavage in a dose of 200 mg/kg, 30 mg/kg, respectively, and every other day for 21 days. Dosage, duration and solvent of DOX, PE and PE‐CSNP administrations were determined according to previous studies (Dhamodharan & Mirunalini, 2013; Shimizu et al., 2006; Tutun et al., 2019). Twenty‐four hours after the end of the experiment, the animals were weighed and decapitation was performed with a guillotine.…”
Section: Methodsmentioning
confidence: 99%